SAT0582 Bone marrow lesion type and pain in knee osteoarthritis. (12th June 2018) - Perry, T.A.; O'Neill, T.W.; Parkes, M.J.; Felson, D.T.; Hodgson, R.; Arden, N.K.
Abstract : Background: Bone marrow lesions (BMLs) have been associated with pain in observational studies of knee OA. The aim of this study was to determine whether type of BML (subchondral, with and without regions of well-defined high post-contrast signal, and ligament-based) were associated with knee symptoms. Objectives: To assess the association between bone marrow lesion volume, including sub-types, and pain in symptomatic knee OA. Methods: Data were collected on a sub-sample of participants who were part of the UK VIDEO study 1 ; a 3 year multicentre randomised placebo-controlled trial of vitamin D therapy in patients with symptomatic knee OA. Those recruited to one of the participating centres (Southampton) had contrast enhanced MR imaging (CE-MRI) of the index knee performed at one or more annual visits. BML volume was assessed by segmentation of sagittal T1-weighted fat-suppressed post-contrast scans. BMLs were categorised by type (subchondral/ligament-based) and by the presence/absence of regions of well-defined high post-contrast signal (for the subchondral BMLs only). As part of the trial, subjects completed the WOMAC questionnaire which included questions on pain, function and stiffness. We used random-effects multiple linear panel regression, adjusting for variance between follow-up visits to explore the relationship between BML volume and the WOMAC pain and function subscales. This approach is preferred over cross-sectional analyses, as it makes use of all available observations from study visits, and controls for within-patient correlations appropriately. Results: In this analysis, we included 50 subjects who had had a baseline MRI and at least one other MRI performed. The mean age of the subjects was 63.3 (SD ±6.5) years and 74% were female. After adjusting for variation between visits, there was no significant association between total BML volume and WOMAC pain when the BMLs were stratified by type; total subchondral BML volume (b=41.5 mm 3 ; 95% CI −19.35 to 102.37) or total ligament-based BML volume (b=9.1 mm 3 ; 95% CI −6.39 to 24.59). Further, we did not observe an association between pain and volume of subchondral BMLs with or without regions of well-defined high post-contrast signal; (i) total mixed subchondral oedema-like BMLs containing regions of well-defined high signal (b=39.45 mm 3 ; 95% CI −3.93 to 82.83) or (ii) subchondral oedema-like BML volume (b=−4.16 mm 3 ; 95% CI −53.49 to 45.18), after adjusting for variation between visits. There was, however, a significant association between the volume of subchondral regions of well-defined high signal and both WOMAC pain (b=2.19 mm 3 ; 95% CI 0.88 to 3.49) and function (b=1.61 mm 3 ; 0.37 to 2.84). Conclusions: In this analysis, an increased volume of regions of well-defined high signal intensity on post-contrast scans within subchondral BMLs was associated with knee pain and function. Reference: [1] Arden NK, Cro S, Sheard S, Dore CJ, Bara A, Tebbs SA, et al. The effect of vitamin D supplementation on knee osteoarthritis, the VIDEO study: a randomised controlled trial. Osteoarthritis Cartilage2016Nov;24(11):1858–66. Disclosure of Interest: None declared